University characteristics associated with the award of places for midwives in the peruvian rural service: Características universitarias asociadas a la adjudicación de plazas para obstetras en el servicio rural peruano - Llanos-Najarro, Elizabeth (2020)
Objective: To determine the university characteristics associated with the allocation of place for obstetricians in the Rural and Urban Marginal Service in Health (SERUMS), 2019. Material and Methods:  secondary base analysis obtained from the Peruvian Ministry of Health, where 506 obstetrics licenses were selected who submitted the National Obstetrics Exam (ENAOBS) and who have applied to SERUMS in the 2019-2 call. The characteristics of the universities where the obstetricians come from, the score obtained in the national and university exam and if it is suitable for SERUMS were evaluated. For the bivariate analysis it will be used in the Students  T, ANOVA and Pearsons Correlation tests, while to adjust the model a logistic regression was performed, a 95% confidence level. Results: The obstetrics  graduate visited mostly from a private university (66.01%), from the Lima region (41.7%) and applied for the paid modality (99.41%). It was found that 49.61% [95%CI: 45.23-53.98] were suitable for SERUMS. The average university qualification was 13.87 ± 1.35 and that of the ENAOBS was 10.93 ± 2.02, which had a significant correlation (p<0.001) that had a greater slope in graduates of public university (R=0.56). Belonging to a public university (OR=2.62) and studying in Lima (OR=1.49) were significantly associated (p<0.01) to be able to perform SERUMS in obstetrics. Conclusions: Being a graduate in obstetrics from a public university and studying in Lima gives you a better chance of being able to award a place in the SERUMS.